(untitled) (Innovative professional education, 2025)
The article describes the relevance of the use of innovative technologies in the professional training of future qualified workers in the food industry. The importance of the use of distance and blended learning in modern conditions as critically important forms of ensuring a continuous educational process in vocational (VET) education is reflected